Effect of Fashion E-Commerce User Experience on Customer Retention in Ghana - Ofori, Michael (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the effect of fashion e-commerce user experience on customer retention in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research indicates that positive user experiences, characterized by intuitive website navigation, efficient mobile interfaces, and responsive customer service, greatly enhance customer retention rates. Users who encounter seamless transactions, personalized recommendations, and reliable delivery services are more likely to return and engage with fashion e-commerce platforms repeatedly. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), self-determination theory (SDT) & expectation-confirmation theory (ECT) may be used to anchor future studies on effect of fashion e-commerce user experience on customer retention in Ghana. Practically, fashion e-commerce platforms should invest in user-friendly website design and navigation to enhance the overall shopping experience. This includes simplifying the checkout process, ensuring mobile compatibility, and improving site speed. From a policy perspective, e-commerce regulations should include guidelines for user experience best practices. This could involve setting standards for website accessibility, data protection, and user interface design to ensure a positive online shopping experience.